The American Jockey, 1865-1910 - Steven A. Riess (Transatlantica)
American jockeys for most of the nineteenth century were African Americans. It was a dangerous occupation that paid extremely well for successful jockeys. These riders were pushed out of this occupation, as jockeys became recognized as important factors in racing results and as it became increasingly lucrative, just as they were pushed out of other desirable jobs in the era of Jim Crow.